Comparing direct restorations utilising fiber reinforced materials in MOD cavities - pilot study - Tekla Sáry; Katalin Nagy (Hungarian Dental Association, 2019)
Objectives: The aim of this preliminary in vitro study was to compare the efficiency of different direct restorative techniques for restoring class II. MOD cavities in molar teeth. Methods: seventy two mandibular third molars were divided into 6 groups (n = 12). Except for the control group (intact teeth, Group 1), in all other groups deep MOD cavities were prepared. The cavities were restored by different direct restorative techniques (Group 2-6). Group 2: conventional resin-based composite (RBC), Group 3: replacing the missing dentine with short-fiber reinforced composite (SFRC) and occlusally covered with 1 mm RBC, Group 4: fiber net inserted in a buccal to lingual direction placed on the base of the cavity and finished with SFRC and RBC, Group 5: SFRC with fiber net placed on top of it in a buccal to lingual direction and finished with RBC, Group 6: fiber net placed circumferentially into the cavity and finished with SFRC and RBC. The specimens were submitted to static load to fracture test. Results: the intact teeth (Group 1) yielded the highest fracture resistance values among all groups. There was no statistically significant difference between Group 1, 3 and 6. In all groups, the fracture pattern was mostly restorable, except for Group 2 showing non restorable fractures predominantly. Conclusions: The application of fiber net circumferentially with SFRC produced fracture resistance values closly resembling the values with intact teeth. Cavities restored with conventional RBC filling showed significantly worse values regarding fracture resistance compared to intact teeth.